New developments in advanced welding - Ahmed, Nasir (Woodhead Publishing in materials., 2005)
Recent developments in high-technology areas have significantly transformed the welding industry. Automation, computers, process control, sophisticated scientific instruments and advanced processing methods are all common in today's modern industry. Today's engineers and technologists have to support complex systems and apply sophisticated welding technologies. This comprehensive new book discusses the changes in advanced welding technologies preparing the reader for the modern industry.